CIRCUMSTANTIAL ADJUNCTS USED IN THE TALE âTHE TAMING OF THE SHREWâ - Nurhasanah, Nurhasanah (STKIP Bina Bangsa Getsempena Banda Aceh, 2017)
The study deals with the use of circumstantial adjuncts in the tale â The Taming of the Shrewâ. The sources of data were adopted from one of the six tales from Shakespeare which are retold by E.F Dood, namely â The Merchant of Veniceâ, âThe Tempestâ, âJulius Caesarâ, âThe Taming of the Shrewâ, âKing Learâ, and âMacbethâ from which âThe Taming of the Shrewâ was taken as sample. Descriptive analysis technique is used to find new evidence to prove the thruth of the story. It is also used to find out the dominant type of circumstantial adjuncts used in the tale. The finding indicates that only eight of the nine types of circumstantial adjuncts were found in the tale. Through the analysis done the dominant type that usually occurs is location. Meanwhile circumstantial adjunct of angel is the only type which is not found in the tale.Â Keywords: Circumstantial Adjuncts